EDUCATION OF YOUNG PEOPLE IN THE SPIRIT OF MILITARY PATRIOTISM - Ulug Tilloyev Umarovich (Journal of new century innovations, 2023)
Abstract: The Republic of Uzbekistan undertakes the tasks of ensuring the safety, peace and stability of citizens while conducting peace policy. According to the Charter of the United Nations, it implements the inviolable right to defense, and provides military and defense power of the state at the level of intellectual sufficiency.